Discovery of highly potent and novel LSD1 inhibitors for the treatment of acute myeloid leukemia: structure-based virtual screening, molecular dynamics simulation, and biological evaluation - Hong, Ye; Wang, Yuting; Hao, Ziyi; Zhang, Xingxia; Si, Yejun; Lin, Guoqiang; Zhang, Shurong; Niu, Miao-Miao; Yang, Xiaotian; Zhang, Yanming (Frontiers in Pharmacology, 2025)
Acute myeloid leukemia (AML) is a highly aggressive hematological malignancy with a significant unmet clinical need for new therapeutic agents. Lysine-specific demethylase 1 (LSD1), a key regulator of leukemia stem cell self-renewal, has emerged as a promising epigenetic target for AML treatment. Herein, we employed an innovative multi-step integrated screening protocol, encompassing pharmacophore modeling, docking screening, molecular dynamics simulation, and biological evaluation, to identify novel LSD1 inhibitors. This comprehensive approach led to the discovery of six potent LSD1 inhibitors (we named these inhibitors LTMs 1–6), with LTM-1 exhibiting the most pronounced inhibitory effects on LSD1 (IC50 = 2.11 ± 0.14 nM) and the highest selectivity for LSD1 over LSD2 (>2370-fold). Notably, LTM-1 demonstrated outstanding antitumor activity both in vitro and in vivo. In vitro, LTM-1 showed potent anti-proliferative effects against LSD1-addicted MV-4-11 leukemia cells (IC50 = 0.16 ± 0.01 μM). In vivo, LTM-1 treatment significantly reduced tumor growth in MV-4-11 xenografted mice. Moreover, LTM-1 did not induce significant changes in liver and kidney function indices, suggesting a favorable safety profile. These results indicate that LTM-1 is a highly promising preclinical candidate for AML treatment, offering a new strategy for the development of more effective and selective LSD1 inhibitors.